If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(b + 3) = 7(b + -3) Reorder the terms: 6(3 + b) = 7(b + -3) (3 * 6 + b * 6) = 7(b + -3) (18 + 6b) = 7(b + -3) Reorder the terms: 18 + 6b = 7(-3 + b) 18 + 6b = (-3 * 7 + b * 7) 18 + 6b = (-21 + 7b) Solving 18 + 6b = -21 + 7b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-7b' to each side of the equation. 18 + 6b + -7b = -21 + 7b + -7b Combine like terms: 6b + -7b = -1b 18 + -1b = -21 + 7b + -7b Combine like terms: 7b + -7b = 0 18 + -1b = -21 + 0 18 + -1b = -21 Add '-18' to each side of the equation. 18 + -18 + -1b = -21 + -18 Combine like terms: 18 + -18 = 0 0 + -1b = -21 + -18 -1b = -21 + -18 Combine like terms: -21 + -18 = -39 -1b = -39 Divide each side by '-1'. b = 39 Simplifying b = 39
| 2n-3=7+4n | | 5-(6/2+1)*2= | | 2(4y-2)=6y | | 18x^2-15x+2= | | 5-(62+1)*2= | | 28.25+18x=19.85+32x | | -6(2x+8)=-12(x-3) | | 1372.50=0.15(x-8700)+870 | | ln(x^2-17)-ln(X-5)=0 | | 140-4x=5x+23 | | 20+5y=5y | | 8-7x=19-14x | | 8-5n=9n | | 5-3(x+4)=x-7 | | 30+x(4)-33=621 | | 9+7+(3-y)i=-4+6i | | 0.90x+.05(12-x)=.10(-45) | | 3(x+4)=0.5x-8 | | 11=-3p-13+4p | | 73-2x=2x+21 | | 3n-1=3.5-9n | | y=-3*2+4 | | 14b-2=19b | | 8x+2*3=6 | | 0.95X+0.5(6-X)=.10(-123) | | 6x+2-2x=6 | | y=-3*1+4 | | (5-6y)+(-9y+2)= | | y=-3*0+4 | | 3=6p-10-5p | | X^2+7X-112=0 | | f=1 |